Resolving out of Africa event for Papua New Guinean population using neural network - Mondal, Mayukh; André, Mathilde; Pathak, Ajai K.; Brucato, Nicolas; Ricaut, François-Xavier; Metspalu, Mait; Eriksson, Anders (Nature communications, 2025)
The demographic history of the Papua New Guinean (PNG) population is a subject of interest due to its early settlement in New Guinea, its relative isolation and substantial Denisovan ancestry. Previous research suggested an admixture with an early diverged out of African population. This study re-examines the PNG population using newly published samples. Our findings demonstrate that the observed shifts in Relative Cross Coalescent Rate (RCCR) curves are driven by strong bottleneck and slower population growth rate of the PNG population, rather than the contributions from an earlier out of Africa population. Although a small contribution from the early out of Africa population cannot be ruled out, it is no longer needed to explain the observed results. Our analysis positions them as a sister group to other East Asian populations. This study provides insights on the PNG population and highlights the impact of population-specific demography on interpreting RCCR curves. Here the authors reveal that a strong bottleneck and slow growth of ancestral effective population size in Papua New Guinean populations can be mistaken for admixture with an earlier out-of-Africa population.